O caráter inovador da Universidade Federal da Integração Latino-Americana a partir da percepção da comunidade acadêmica - Oliveira, Michelle Cristina Martins de (2019)
Social inequalities are present as deep marks in Brazilian and Latin American society. It is a complex and multifaceted phenomenon that impacts various sectors of the social structure and organization of all these countries. Although not the main object of the research, there is a reverberation of social inequalities also in education. Currently, in Brazil, we still have a very low number of people with access to higher education. The process is dialectical: there is a maintenance of groups in power throughout the history and those groups have access to quality education, while marginalized groups remain in these subordinate positions. Changes in the social environment, such as the development of a globalized world, increase the demand for access to higher education. In this perspective, we can verify the need to innovate in education. We understand that innovation starts from the unveiling of society, fundamentally with the development of critical awareness. It is a process of breaking the current scenario, with the intention of a praxis that contributes to a fairer society, with equity. In order to have this happening, in a university, it is necessary to work in five areas: management, curriculum, efficient teaching methodology that departs from the reality of being of the students, environment and intersectoriality. By presenting a differentiated project, we intended to respond, through the speech of members of the institution, whether the Federal University of Latin American Integration - UNILA could be characterized as an innovative institution. To this end, we conducted semi-structured interviews that were later analyzed using the content analysis method. Made the categories, it was concluded that the institution presents characteristics of an innovative educational environment especially when considering the current social conjuncture